Father's Role in Building Son Sholeh in The Study of Luqman's Letter Verses 12-19 - Kurniawan, Ade; Rhain, Ainur (Universitas Muhammadiyah Surakarta, 2023)
The assumption that the role of the father is only the breadwinner results in the lack of responsibility of the father in the education of children. On the other hand, the Quran tells a lot of advice from fathers to their children in education and morals. This indicates that the Qur'an encourages fathers to always play a role in the education of children. The purpose of this study is to analyze the advice of a father towards a child in the Quran, namely in Sura Luqman verses 12-19. The approach used in analyzing such data is the use of code theory models and messages. The conclusion in this study is that the analysis on this theory gives birth to father advice to children can be seen from six factors, namely: (1) Good sender; (2) Good recipients; (3) Messages that vary from the introduction of Tawhid, Amal Salih and Morals; (4) The context of the situation behind all advice; (5) The use of calling words spoken in soft words; (6) The existence of good mutual contact.